Investigation of characteristics of spark ignition engine fuelled with ethanol-gasoline blends using Iso-octane additive - Delvi, Hamza Afser; Faheem, Mohammed; Aabid, Abdul; Math, M.C.; Khan, Sher Afghan (Akademia Baru, 2020)
The quick depletion of petroleum reserves rises in automobile emissions, and an increase in costs and concerns for the environment has prompted a relentless quest to substitute fuels. For Gasoline, one of the best alternatives is found to be Ethyl Alcohol. As it is obtained from biomass crops enriched with starch, sugar, and cellulose material. These crops are renewable and pollution-free. The nature of ethyl alcohol is the same as compared to petrol. Both are liquid, and in this way, storage and transport are similar. Both can be blended expertly and burnt. In the present study, E30 (30% Ethanol + 70% Gasoline) blend was used and tests were carried out for a single-cylinder, 4- stroke, computerized spark-ignition (SI) gasoline engine fitted with eddy current dynamometer. Further, a precisely adjusted exhaust gas analyzer and the performance, combustion, and emission characteristics of the Spark Ignition Engine were recorded in “Enginesoft” software. In order to reduce the problem of knocking in the Spark Ignition Engine, along with E30 Blend, Iso-Octane additive, which is an excellent anti-knocking agent, was added in 0.3%, 0.4% and 0.5% by volume, i.e., E30+0.3, E30+0.4 and E30+0.5 respectively.